Open-Circuit Fault-Tolerant Method for Half-Bridge Switches of Three-Level Quasi-Switched Boost T-Type Inverter to Improve Voltage Gain - Duc-Tri Do; Khai M. Nguyen; Vinh-Thanh Tran (IEEE Access, 2024)
The three-level quasi-switched boost T-type inverter (3L-qSBT2I) can feature buck-boost operating and shoot-through (ST) immunity with high voltage gain and low component voltage rating. In order to improve the reliability of 3L-qSBT2I, this paper proposes an open-circuit fault-tolerant (OC-FT) method to solve OC faults of semiconductor devices. Under this approach, OC faults of half-bridge switches of the T2I branch are addressed. To solve these faults, one extra normally-closed (NC) relay is integrated with the 3L-qSBT2I, which connects neutral points of DC-link voltage and inverter side. In normal condition, this relay is closed and the inverter operates like a conventional 3L-qSBT2I. In post-fault operation, this relay is opened and the inverter operates like a two-level inverter. A new two-level space vector modulation (SVM) scheme is introduced to control this inverter. Unlike any traditional OC-FT methods, in this proposed method, almost large voltage vectors are still used, in post-fault operating. Therefore, the voltage gain of the proposed method is increased compared to others. Comparison study and experimental results are presented to validate the proposed topology and FT method.